Tinjauan ‘Urf terhadap Hukum yang Mengatur Praktik Pernikahan Adat Pakake Anak Daro dalam Suku Mandailing - Nst, Ade Irma Putri; Lubis, Azwani (Fakultas Hukum, Universitas Muslim Indonesia, 2024)
This research investigates the alignment of ‘urf with Islamic law in the context of the Pakake Anak Daro customary marriage among the Mandailing tribe in Singkuang Village. Adopting a mixed-method approach, the study explores the role of ‘urf within this marriage practice and its adaptation to modern times. Findings reveal that Pakake Anak Daro is a meaningful customary marriage rich in cultural values. It encompasses various processions, spanning pre-wedding, wedding, reception, and post-wedding stages, serving to strengthen cultural identity, foster social bonds, and express gratitude to Allah. The practice fulfills the ‘urf sahih (valid) criteria in Islamic law, embodying benefits, widespread acceptance, historical roots, and non-contradiction with Sharia principles. Pakake Anak Daro exemplifies the harmonious coexistence of local traditions and religious principles, contributing to Indonesia’s rich cultural tapestry. The study recommends collaboration among the Government, Religious Leaders, Customary Leaders, and Indigenous People to safeguard and promote this customary marriage as an integral part of Indonesia’s cultural heritage.